2017
DOI: 10.1016/j.bbadis.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid inhibits human erythroid 5-aminolevulinate synthase: Molecular mechanism and tolerance study with four X-linked protoporphyria patients

Abstract: Mutations in the C-terminus of human erythroid 5-aminolevulinate synthase (hALAS2), a pyridoxal 5'-phosphate (PLP)-dependent enzyme, are associated with two different blood disorders, X-linked sideroblastic anemia (XLSA) and X-linked protoporphyria (XLPP). XLSA-causing mutations yield hALAS2 variants with decreased activity, while XLPP-causing mutations result in a gain-of-function of hALAS2. There are no specific treatments for XLPP. Isonicotinic acid hydrazide (isoniazid, INH), an antituberculosis agent, can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…34 The antituberculosis agent isoniazid (INH) is a potent inhibitor of the ALAS2 enzyme and may induce sideroblastic anemia in some patients. 35 It was recently shown that INH reduces PPIX accumulation in cellular and murine models of protoporphyria. 36 However, pilot clinical studies failed to confirm the therapeutic effect in patients with XLP and EPP after administration of INH at the standard treatment dose (5 mg/kg per day, up to 300 mg/d) for Mycobacterium tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…34 The antituberculosis agent isoniazid (INH) is a potent inhibitor of the ALAS2 enzyme and may induce sideroblastic anemia in some patients. 35 It was recently shown that INH reduces PPIX accumulation in cellular and murine models of protoporphyria. 36 However, pilot clinical studies failed to confirm the therapeutic effect in patients with XLP and EPP after administration of INH at the standard treatment dose (5 mg/kg per day, up to 300 mg/d) for Mycobacterium tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…ABCB7 exports [2Fe–2S] clusters out of the mitochondria and into the cytosol, and ABCB7 deficiency causes an iron-deficient phenotype and mitochondrial iron accumulation [ 79 , 80 ]. Indeed, sideroblastic anemia responsive to vitamin B 6 administration is reported with antitubercular therapy [ 8 , 9 , 10 ], and multiple types of anemia (including iron-deficiency anemia) occur with antitubercular therapy [ 81 , 82 , 83 ]. These data and previous reports suggest that isoniazid and rifampicin lead to an iron-deficient state, with concomitant changes in heme biosynthesis regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatotoxicity is a leading cause of TB therapy treatment failure, with up to 28% of all anti-TB treatment failure attributed to toxicity [ 3 , 4 ]. Antitubercular therapy may also be associated with acute intermittent porphyria [ 5 , 6 ], sideroblastic anemia [ 7 , 8 , 9 , 10 ], hypercoagulability [ 11 , 12 , 13 ], peripheral neuropathy [ 14 , 15 , 16 ], porphyria cutanea tarda [ 17 ], vitamin B 3 deficiency [ 18 , 19 , 20 ], and vitamin B 6 deficiency [ 8 , 14 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some patients with EPP have described worsening of photosensitivity after iron administration, but associated changes in protoporphyrin levels have not been studied prospectively. D) Alternatively, reducing haem and haemoglobin synthesis through erythrocyte transfusion, haem infusion, hydroxyurea, iron suppression or direct inhibition of ALAS2 95 might ameliorate all erythropoietic porphyrias by reducing synthesis of porphyrin intermediates. 5 In this regard, improvement was reported using haem transfusion and hydroxycarbamide (hydroxyurea) in ADP 11 and congenital erythropoietic porphyria, 96 and iron reduction in a patient with congenital erythropoietic porphyria.…”
Section: )mentioning
confidence: 99%